2007
DOI: 10.1186/cc6089
|View full text |Cite
|
Sign up to set email alerts
|

Urine neutrophil gelatinase-associated lipocalin is an early marker of acute kidney injury in critically ill children: a prospective cohort study

Abstract: Introduction Serum creatinine is a late marker of acute kidney injury (AKI). Urine neutrophil gelatinase-associated lipocalin (uNGAL) is an early marker of AKI, where the timing of kidney injury is known. It is unknown whether uNGAL predicts AKI in the general critical care setting. We assessed the ability of uNGAL to predict AKI development and severity in critically ill children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
276
3
13

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 374 publications
(309 citation statements)
references
References 31 publications
(42 reference statements)
17
276
3
13
Order By: Relevance
“…In this case-control study of AKI in preterm infants, we found that urinary biomarkers were associated with AKI, defined Urine NGAL has been recently reported to be a useful early AKI marker that predicted development of severe AKI in a heterogeneous group of pediatric patients admitted to the PICU with unknown timing of kidney injury (15). A multicenter pooled analysis of prospective studies shows that NGAL can predict mortality even in the absence of diagnostic increases in serum creatinine (16).…”
Section: Discussionmentioning
confidence: 67%
“…In this case-control study of AKI in preterm infants, we found that urinary biomarkers were associated with AKI, defined Urine NGAL has been recently reported to be a useful early AKI marker that predicted development of severe AKI in a heterogeneous group of pediatric patients admitted to the PICU with unknown timing of kidney injury (15). A multicenter pooled analysis of prospective studies shows that NGAL can predict mortality even in the absence of diagnostic increases in serum creatinine (16).…”
Section: Discussionmentioning
confidence: 67%
“…It was shown previously in many clinical studies and has been accepted that NGAL and Cystatin C levels increase in different clinical settings leading to AKI development [10][11][12][13][14][15][16][17][18][19][20][21][22]. Since the aim of this study is to define the roles of Cystatin C and NGAL in predicting septic AKI development, the patients who had other risk factors, rather than sepsis, that would lead to AKI and increase the Cystatin C and NGAL levels (i.e., nonseptic-AKI patients) were excluded from the study.…”
Section: Exclusion Criteriamentioning
confidence: 98%
“…They concluded that urine NGAL is probably a more robust marker of AKI than plasma NGAL in patients with septic shock since urine NGAL levels remain within normal limits even when plasma levels are high and signs of AKI are absent. Previous studies on pediatric ICU patients have also shown that serum NGAL is a nonspecific predictor [19] and urine NGAL is a good predictor of AKI [13]. Bagshaw et al, also studied plasma and urine NGAL levels in early diagnosis of AKI in septic patients [15].…”
Section: Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…19 In adult cardiac surgery and critically ill children, the predictive ability of these urinary biomarkers for early diagnosis of AKI have been modest, largely reflecting the greater complexity of these populations. [20][21][22][23] Recently, in a prospective study of 635 adults presenting to the emergency department, a single elevated urinary NGAL was shown to predict a composite of development of AKI and the need for RRT, nephrology consultation, and/or ICU admission. 24 Similarly, serum NGAL and cystatin C have been found to be promising diagnostic biomarkers for early detection of AKI in a range of clinical settings, including cardiac surgery, contrast-induced nephropathy, and sepsis.…”
Section: Acute Kidney Injury Predictionmentioning
confidence: 99%